Influence of fungicides on the introduction of hazelnut shoots in in vitro - R. S. Rakhmangulov; N. A. Urazbakhtina; T. A. Simonyan; A. O. Matskiv; G. A. Tsaturyan (Новые технологии, 2019)
The article presents original data on the development of methods for producing sterile viable hazelnut explants. It is well known that one of the difficult stages of clonal micropropagation of tree crops is the stage of introducing in vitro into the culture due to the strong contamination by endogenous fungi, excessive sterilization and oxidation of explants. As a result, the aim of the work is to determine the degree of influence of various fungicides on the growth of a pure culture of fungal plant pathogens under the invitro condition, as well as processing hazelnut shoots to obtain a sterile culture.As a result of the studies, it has been found that the number of pure viable explants is 10-44 % with pretreatment of shoots with fungicides, depending on the type of fungicide. In the control variant, the number of viable explants is 0 %.Significant results have been obtained when processing with such preparations as Scenic, Klad and Lamador, where the percentage of sterile viable explants varies in the range of 42-44 %. These results will be useful in the process of forming a deposited collection of economically useful hazelnut genotypes under in vitro conditions and developing regulations for clonal micropropagation. The data obtained will serve as the basis for further research.